Druhý břeh západu. výbor iberoamerických esejů. [the second coast of the West: Anthology of ibero-American essays.] introduction and editing by Anna Housková.: Prague: Mladá fronta, 2004, ISBN: 80-204-1139-9, 372 pages. - Halbich, Marek (Lidé města, 2011)
A review of the book.